2017
DOI: 10.21815/jde.016.016
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Attitudes Toward Tobacco Cessation in the Dental Setting: A Systematic Review

Abstract: Many dental schools have integrated tobacco cessation into their predoctoral curricula. However, dental students' perceptions should be taken into consideration when designing those curricula. The aim of this study was to systematically review the published literature on dental students' attitudes and perceptions regarding tobacco cessation. The research team conducted a search for articles through April 2016 using the following electronic databases: Medline, PsychInfo, Cochrane Library, and CINAHL. Each abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
(139 reference statements)
1
13
1
1
Order By: Relevance
“…Attitude scores of the study subjects towards counselling for helping patients quit Tobacco in the present study was around 65%, which is similar to that reported by Cannick et al, (2006), McCartan et al, (2008, Anders et al, (2014) and Halawany et al, (2013) but contrasting to that reported by Uti and Sofola (2011), who reported low attitude scores among Nigerian dental students. In a systematic review on the attitudes of dental students towards the provision of Tobacco cessation services, Virtue et al, have reported that students were positively inclined towards the same (Virtue et al, 2017). The results of the present study are encouraging as it indicates that the respondents have a positive inclination towards counselling individuals with Tobacco use.…”
Section: Discussionsupporting
confidence: 65%
“…Attitude scores of the study subjects towards counselling for helping patients quit Tobacco in the present study was around 65%, which is similar to that reported by Cannick et al, (2006), McCartan et al, (2008, Anders et al, (2014) and Halawany et al, (2013) but contrasting to that reported by Uti and Sofola (2011), who reported low attitude scores among Nigerian dental students. In a systematic review on the attitudes of dental students towards the provision of Tobacco cessation services, Virtue et al, have reported that students were positively inclined towards the same (Virtue et al, 2017). The results of the present study are encouraging as it indicates that the respondents have a positive inclination towards counselling individuals with Tobacco use.…”
Section: Discussionsupporting
confidence: 65%
“…This lack of continuity of care entails an enhanced indication for dental health professionals to take over responsibility for counselling and supporting their patients. A recent systematic review about dental students’ views on tobacco cessation in a dental setting showed that they were more likely to put the first two As (ask, advise) of the 5A approach into action and did not engage as much in assessing readiness to quit, assisting in a quit attempt and arranging for follow‐up. These results were based on surveys rather than objective assessments of behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Global Health Professions Student Survey (GHPSS) showed that most health professional students did not feel sufficiently prepared to counsel smokers in a professional way . At the same time, a majority of dental students appear to be interested in being trained in tobacco cessation . Despite interest and necessity, less than 40 percent of dental students have ever received such training .…”
Section: Introductionmentioning
confidence: 99%
“…These findings may partly explain the low level of adherence to tobacco use cessation guidelines among oral health professionals [ 32 - 35 ]. Effective tobacco cessation training should include skills and strategies that address student perceptions to foster the belief that tobacco cessation efforts are a part of quality clinical practice [ 36 ]. There is evidence that the training of health professionals in interventions for smoking cessation is associated with an increase in the smoking cessation rate [ 37 ].…”
Section: Discussionmentioning
confidence: 99%